Aetiology of new onset seizures in cases admitted to an intensive care unit of a tertiary care hospital: a two year study - Pannem, Ramesh Babu; Chintha, Venkata Subrahmanyam (International Journal of Advances in Medicine, 2019)
Background: Seizures are a common neurological disorder encountered globally in regular medical practice. Hospital onset seizures may occur in patients who never had a history of seizure before hospitalization and may be due to causes that lead to hospitalization or acquired during hospitalization like stroke, neuro infection etc. The objectives of this study were the purpose of the present study was to study the incidence and to describe demographic and clinical characteristics of patients developing new onset seizures in an intensive care unit of a tertiary care hospital. Methods: A prospective study for two years was conducted on cases of seizures admitted in an intensive care unit of a tertiary care hospital. The etiology of all the cases was recorded based on the clinical history and necessary investigations like EEG and imaging studies of the brain in cases if required. Results: About 238 cases with males 177 and females 61 cases were enrolled, and 31-50 years was most common age group. Diabetes was the most common co morbidity associated and generalized seizures were most common. CVA was most common etiology (26.89%) and idiopathic next common. Infarct was most common cause of CVA and meningitis in infections. Generalized tonic clonic seizures was most common in cases with CVA as the aetiology followed by infective cases. Conclusions: It is mandatory to deal cautiously and carefully the cases of seizures developing in an ICU in addition to proper history and examination, each patient must undergo detailed EEG, imaging investigations and other ancillary investigations if necessary.